Cameroon : Financial System Stability Assessment; Update. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses details of Cameroon' Financial System Stability Assessment (FSSA). The FSSA is based on the work of a joint IMF-World Bank mission that visited Cameroon as part of the Financial Sector Assessment Program in June 2007. Excess liquidity may be inducing banks to narrow their margins. The lower spread and reduced profitability tilted domestic banks toward disintermediation and discouraged them from opening new branches. The efficiency of the supervisory framework suffers from the limited institutional independence of the Central African Banking Commission.